Fungi mediated production and practical purification of (R)-(-)-3-quinuclidinol - Kolet, Swati P.; Jadhav, Dipesh D.; Priyadarshini, Balaraman; Swarge, Bhagyashree N.; Thulasiram, Hirekodathakallu V. (Tetrahedron Letters, 2014)
A fungal system belonging to Mucoraceae family (Mucor piriformis) was explored for the asymmetric reduction of a prochiral ketone, 3-quinuclidinone (I) in an efficient manner to produce an important pharmaceutical precursor (R)-(-)-3-quinuclidinol (II) with similar to 96% enantiomeric excess. The efficiency of the process was improved by developing a cation exchange resin (Amberlite IR-120) which assisted the purification of water soluble metabolite II from fermentation media. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: (R)-(-)-3-Quinuclidinol; Amberlite IR-120; Biotransformation; Ion exchange resin; Mucor pinformis